Hepatocyte growth factor/c-Met signalling is important for the selection of transplanted hepatocytes - Kaldenbach, Michaela; Tschaharganeh, Darjus-Felix (Gut, 2012)
Background: At present hepatocyte transplantation is a promising option for cellular therapy of end-stage liver diseases. However, the underlying molecular mechanisms need to be better defined in order to translate this technique into clinical use. This study investigated the cursiv relevance of hepatocyte growth factor (HGF)/c-Met signalling for hepatocyte repopulation after transplantion. Methods: Wild-type mice (c-MetloxP/loxP) and hepatocyte-specific conditional c-Met (HGF receptor) knockout (c-MetΔhepa) mice were used as donors and recipients for hepatocyte transplantation. Results: Transplantation experiments revealed two major findings. First it was demonstrated that c-Met is indispensable in donor cells, as c-MetΔhepa cells did not repopulate recipient livers after transplantation. Second, genetic deletion of c-Met in recipient hepatocytes resulted in enhanced expansion of unmodified donor cells in host livers (up to 250-fold after 12 weeks). The relevant mechanisms for this observation in c-MetΔhepa host hepatocytes could be defined. c-MetΔhepa hepatocytes showed enhanced apoptosis, reduced cellular proliferation and a lack of AKT-kinase and STAT3 activation. In addition, tissue remodelling was changed in c-MetΔhepa recipient livers. Therefore, the lack of pro-proliferative transcription factors, increased apoptosis and changes in matrix-remodelling inhibit host cell proliferation in c-MetΔhepa recipient livers and thus favour repopulation of transplanted hepatocytes. Therapeutically liver repopulation could be increased through adenoviral expression of NK-4—an inhibitor of HGF signalling—in host hepatocytes. Conclusion: HGF/c-Met plays a crucial role in host and donor cells of the liver for the cursiv selection of transplanted hepatocytes. Modulating HGF-dependent signalling seems a promising therapeutic option to favour expansion of transplanted hepatocytes.
Published online first 27 January 2012
Gesehen am 14.07.2018